Multiple criteria decision making (MCDM) methods in economics: an overview - Zavadskas, Edmundas Kazimieras; Turskis, Zenonas (Technological and Economic Development of Economy, 2011)
The main research activities in economics during the last five years have significantly increased. The main research fields are operation research and sustainable development. The philosophy of decision making in economics is to assess and select the most preferable solution, implement it and to gain the biggest profit. Preferences are used in a lot of problem situations both in individual and organizational decision making processes. A number of effective decision making methods that support decisions under conditions of multiple criteria have appeared in the last decade. This paper presents a panorama of decision making methods in economics and summarizes the most important results and applications over the last five years. This paper considers decision making in light of the recent developments of multiple criteria decision making methods (because classical methods are overviewed in a lot of earlier publications). Authors of different approaches, pioneering studies and works are presented in short. Article in English. Daugiatiksliai sprendimų priėmimo metodai ekonomikoje: apžvalga Santrauka. Priimant ekonominius sprendimus pagrindinis tikslais gali būti: įvertinti tikslingas altrenatyvas, parinkti geriausią alternatyvą, įgyvendinti parinktą sprendimą ir gauti didžiausią naudą. Sprendimus gali parinkti tiek atskiri veikėjai tiek ir veikėjų grupės. Vertinamų sprendimų pasekmės įtakoja tiek sprendėjų tiek ir visuomenės poreikius. Šiame straipsnyje pateikiama sprendimų priėmimo metodų, kuriuos galima taikyti ekonomikoje, apžvalga. Straipnyje pateikiama paskutinių penkerių metų svarbiausių tyrimų apžvalga. Taip pat pristatyti populiariausių daugiatikslių sprendimų priėmimo metodų, kurie taikomi ir kuriuos galima taikyti priimant sprendimus ekonomikoje, autoriai. Reikšminiai žodžiai: daugiatikslis sprendimų priėmimas, ekonomika, analizė, apžvalga.